PERAN MAHASISWA KKN UNP DALAM EDUKASI BELAJAR ANAK MELALUI LES PRIVAT DI JORONG LOMPEK NAGARI HALABAN KABUPATEN LIMA PULUH KOTA - Muhammad Yusuf Alhamdani; Ratna Wilis; Lidyawati Novita Simatupang; Adella; Nayla Khairiatul Ramadhani; Tina Arnasti; Azka Zafarani Fadhilah; Jihan Roobiaht (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Community Service is a form of student service to the community through the application of knowledge and learning experiences in a real social environment. Through this activity, students are expected to be able to identify and help overcome problems in the community, especially in the field of education. One of the problems found in Jorong Lompek Nagari Halaban, Lareh Sagu Halaban District, Limapuluh Koto Regency is the educational gap, where many children need additional learning assistance outside of school hours. Responding to this, Community Service students from Padang State University implemented a private tutoring program as an effort to improve the quality of children's learning. This program is carried out through personal and intensive tutoring aimed at improving understanding of lesson concepts, assisting with completing school assignments, and fostering learning motivation. In addition to academic aspects, this activity also focuses on developing self-confidence and interest in continuous learning. It is hoped that this program will have a positive impact on children's educational development.